2010
DOI: 10.1074/jbc.m110.101469
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Mono-ubiquitinates Bcl-2 and Regulates Autophagy

Abstract: Parkin is an E3 ubiquitin ligase that mediates the ubiquitination of protein substrates. The mutations in the parkin gene can lead to a loss of function of parkin and cause autosomal recessive juvenile onset parkinsonism. Recently, parkin was reported to be involved in the regulation of mitophagy. Here, we identify the Bcl-2, an anti-apoptotic and autophagy inhibitory protein, as a substrate for parkin. Parkin directly binds to Bcl-2 via its C terminus and mediates the mono-ubiquitination of Bcl-2, which incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 51 publications
2
118
1
Order By: Relevance
“…In another study, it was found that while Parkin overexpression stimulates CCCP-induced mitophagy, it appears to inhibit bulk autophagy under basal conditions. 65 This observation suggests that Parkin may differentially regulate distinct types of autophagy.…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 93%
“…In another study, it was found that while Parkin overexpression stimulates CCCP-induced mitophagy, it appears to inhibit bulk autophagy under basal conditions. 65 This observation suggests that Parkin may differentially regulate distinct types of autophagy.…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 93%
“…The EGFP, EGFP-parkin, EGFP-parkin K161N, EGFP-parkin T240R, Flag, Flag-parkin, and EGFP-p62 constructs have been previously described [26,27] .…”
Section: Plasmidsmentioning
confidence: 99%
“…However, the precise role of Parkin in the induction of mitophagy has not been fully elucidated. To date, several mitochondrial proteins, voltage-dependent anion channel 1 (VDAC1) (8), mitofusin (a mitochondrial pro-fusion factor) (11,14,15), Bcl-2 (16), and Drp1 (17), have been shown to be ubiquitinated by Parkin. Ubiquitination of VDAC1 may recruit the autophagy adaptor p62, which interacts with microtubule-associated protein light chain 3 (LC3) on the autophagosomal membrane (8); however, the requirement of p62 remains controversial (18 -21).…”
mentioning
confidence: 99%